ESTIMASI DAYA DUKUNG LINGKUNGAN KERAMBA JARING APUNG, DI PERAIRAN PULAU SEMAK DAUN KEPULAUAN SERIBU, DKI JAKARTA - Bramana, Aditya; Damar, Ario; Kurnia, Rahmat (Jurnal Teknologi Perikanan dan Kelautan, 2015)
This research describing about the estimation of carrying capacity of water environment against cultivation activities, whereas the type of fish that has been cultivated was grouper fish. Organic waste estimation and carrying capacity of water environment prediction were used to analyze this research. This research resulting that waste loads from cultivation activities were equal to 1.04 kg N/ day/ unit and the estimation of anthropogenic waste loads were 20.56 kg N/ day. Based on approach of waste loads N, carrying capacity of water environment of Semak Daun Island against cultivation activities is 114 units of floating net cages. Assumed a unit of floating net produce of 300 kg of fish, it acquired 28.20 tonnes of fish production can was accommodated.